Persepsi Orang Tua Terhadap Pentingnya Pembentukkan Karakter Pada Anak Usia Dini Di Kelurahan Jatiranggon Bekasi - Choiriyah, Choiriyah; Fitriasari, Anisya; Yuntina, Lily (CV. ITTC INDONESIA, 2024)
Parents' Perception of the Importance of Character Building in Early Childhood in Jatiranggon, Bekasi (2024). Thesis. Jakarta: Faculty of Education, Early Childhood Education, Panca Sakti University Bekasi. 2024. This research aims to understand parents' perceptions of character building in children and to determine whether parents consider character building in children important or not. The research uses a qualitative approach with a descriptive method to obtain an in-depth understanding of how parents shape their children's character at home. Data were collected through interviews, observations, and documentation during the activities. The results of the study show that the representatives of parents in Jatiranggon agree that character building in children is very important, so that children can develop positive behaviors in their future lives.